Modifications of the visual function and life quality in cataract operated patients - Seydu Berthe; Danay Duperet Carvajal; Ana Margarita Hormigó Belett; Ludmila Pérez Castillo; Yamirka Rodríguez Alonso (Centro Provincial de Información de Ciencias Médicas, 2019)
A descriptive and cross-sectional study of 250 operated patients due to senile cataract was carried out in the Ophthalmological Center in Santiago de Cuba, from January, 2015 to February, 2017 to determine the existence of modifications in the visual function and life quality of those affected patients. The following variables were analyzed: age, sex, best corrected visual acuity, colors vision, sensibility to contrast, functional evaluation and life quality before and after surgery. Absolute and relative frequencies were used as summary measures, as well as Chi-squared test of independence and homogeneity, to identify the statistically significant association. The male sex and the ages from 70 to 79 years prevailed. The visual function improved significantly after the surgery, what provided a better life quality, elevating the functional capacity, independence and autonomy of these aged patients.